Pendekatan Kuantitatif dengan Penelitian Survei : Studi Kasus dan Implikasinya - Emilia Kurniawati; Sulastri Rini Rindrayani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Survey research is one of the methods often used in social sciences, education, and various other fields to collect data efficiently from large populations. This study aims to describe the concept, steps, types, advantages, and disadvantages of survey research, and provide guidance in selecting representative samples. The method used in this study is a literature review with a descriptive analysis of relevant theories. The results of the study indicate that survey research has the advantage of being able to collect large amounts of data quickly and support statistical analysis. However, this method also has weaknesses such as the risk of sampling bias and limitations in extracting in-depth information. The implications of this study are the need for careful design, including the selection of appropriate sampling techniques and the development of valid instruments, to improve the quality of survey research. This study is expected to provide practical guidance for researchers in designing and implementing effective and ethical survey research.